2021
DOI: 10.13075/ijomeh.1896.01805
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of cigarette, e-cigarette and heated tobacco use among police employees in Poland: a 2020 cross-sectional survey

Abstract: Objectives: Uniformed services such as police employees are exposed to acute and chronic stressful events at work that may lead to tobacco use. This study aimed to assess the prevalence of cigarette smoking, e-cigarette use and heated tobacco use among police employees in Poland, and to investigate personal characteristics associated with tobacco or e-cigarette use. Material and Methods: This cross-sectional study was carried out in June-July 2020 on a randomly selected sample of 8789 police employees from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Similarly, studies conducted in other countries have also found high tobacco use among police officers [31]. In a recent study conducted by Jankowski et al [32] in the Mazovian Voivodeship of Poland, it was revealed that half of the police employees had ever smoked cigarettes, with one-fifth of them being daily smokers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Similarly, studies conducted in other countries have also found high tobacco use among police officers [31]. In a recent study conducted by Jankowski et al [32] in the Mazovian Voivodeship of Poland, it was revealed that half of the police employees had ever smoked cigarettes, with one-fifth of them being daily smokers.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, smoking cigarettes was also found to be more prevalent among men, although there were no statistically significant differences observed. Moreover, higher odds of daily cigarette smoking were observed among respondents living in cities with populations of 20 000-100 000 and >500 000 compared to those living in rural areas [32]. Furthermore, a higher prevalence of daily cigarette smoking was observed among respondents who reported living alone (24.7%).…”
Section: Discussionmentioning
confidence: 90%
“…The prevalence in some countries such as China is around 0.9%, Poland 3.1%, Malaysia 3.2%, and South Korea 7.6%. Among adolescents, the prevalence of e-cigarette use is related to smoking status (Hod et al, 2022;Jankowski, Gujski, Pinkas, Opoczyńska-Świeżewska, Krzych-Fałta, Lusawa, & Raciborski, 2021;Rahman, Yusoff, Mohamed, Naidu, Lim, Tee, & Aris, 2019;Tam, & Brouwer, 2021;Xiao, Yin, Di, Nan, Lyu, Wu, & Li, 2022). The highest current prevalence of e-cigarette use in Southeast Asia is in Indonesia (11.8%), while the lowest prevalence is in Thailand (3.3%).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them resemble USB flash drives, pencils and other commonplace goods [ 25 ]. Prevalence of current e-cigarette users ranges from 0.9% [ 26 ], 3.1% [ 27 ], 3.2% [ 28 ], and 7.6% [ 9 ], in China, Poland, Malaysia and South Korea respectively. Interestingly, the prevalence e-cigarette use among youth was associated with smoking status [ 29 ].…”
Section: Introductionmentioning
confidence: 99%